2019
DOI: 10.3390/rs11030263
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere Boundary Layer Height (ABLH) Determination under Multiple-Layer Conditions Using Micro-Pulse Lidar

Abstract: Accurate estimation of the atmospheric boundary layer height (ABLH) is critically important and it mainly relies on the detection of the vertical profiles of atmosphere variables (temperature, humidity,’ and horizontal wind speed) or aerosols. Aerosol Lidar is a powerful remote sensing instrument frequently used to retrieve ABLH through the detection of the vertical distribution of aerosol concentration. A challenge is that cloud, residual layer (RL), and local signal structure seriously interfere with the lid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Dang et al [56] defined an objective upper limiter altitude to reduce the interference of RL and cloud layer on daytime MLH retrieval. The top limiter altitude is determined according to the cloud location, whether the cloud is outside or within the ABL is classified through judging if the strongest signal gradient below the cloud base is lower than a preset threshold.…”
Section: Height Restriction For Some Classical Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dang et al [56] defined an objective upper limiter altitude to reduce the interference of RL and cloud layer on daytime MLH retrieval. The top limiter altitude is determined according to the cloud location, whether the cloud is outside or within the ABL is classified through judging if the strongest signal gradient below the cloud base is lower than a preset threshold.…”
Section: Height Restriction For Some Classical Methodologiesmentioning
confidence: 99%
“…The robustness of the technique is based on utilizing the whole backscatter profile rather than the profile surrounding the top of ML [51]. Relatively, the FIT is less sensitivity to local signal structures than the methods directly based on the gradient [55,56]. However, the method is more suitable when ABL with structures that match the particular idealized profile.…”
Section: Ideal Profile Fitting (Curve Fitting) (Fit)mentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these approaches has its limitations regarding the measurement range and accuracy, spatial and temporal resolution, and weather conditions (clouds, fog, and precipitation). The ABLH measurement range and accuracy issues were solved to a large extent with the development of the light detection and ranging technology, e.g., by using next-generation high-power lidars [25][26][27] or low-power lidars and ceilometers [28][29][30][31]. The latter are recognized worldwide as efficient and affordable ground-based instruments for profiling of the atmosphere [32].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies reported in the literature focus on ABLH retrieval during the daytime and for fair-weather conditions [24,28,34,[37][38][39][40] while retrievals during complex weather situations, as well as during the sunrise/sunset and at nighttime, have been performed less often [27,29,31,46]. The most complex boundary layer and aerosol conditions often form at night, which is regarded as an important part of the diurnal changes within the ABL, and thus the nocturnal boundary layer should not be excluded from the ABLH statistical analysis.…”
Section: Introductionmentioning
confidence: 99%